Proposed Marketing Strategy to Increase Brand Awareness of Seruni Hotel, Bogor - Selwin Malta Tanaga (Publikasi Indonesia, 2025)
Puncak Bogor is one of the most popular tourist destinations because it offers natural beauty and is close to the capital city of Jakarta. After the Covid pandemic, the number of tourists visiting Puncak Bogor is estimated at 10,960,348 people, an increase of 166% from 2021, but its not align with the occupancy rate of hotel rooms. This condition is exacerbated by increasing competition with many hotel competitors in Puncak Bogor. Hotel Seruni is one of the long-established lodging providers, but faces the same problem. Hotel Seruni faces challenges regarding brand awareness and marketing existing service products, resulting in a decrease in room occupancy rates because potential customers do not know the existence of the hotel. This research aims to enhance Seruni Hotel’s brand awareness, analyze key factors influencing purchase intention, and develop effective marketing strategies to increase the brand value of Seruni Hotel, also improving its room occupancy performance. This study applies quantitative analysis to assess customer behavior and test hypotheses, with data analyzed through SMART PLS, as well as qualitative methods to gather insights from internal company sources. The research findings indicate that every aspect of the marketing mix has a positive influence on brand awareness. These findings lead to recommendations such as improving products and services, enhancing human resource quality, optimizing promotional channel activities, and utilizing advertising to reach a broader audience. The proposed marketing strategies are developed based on both internal and external analyses, including SWOT and TOWS frameworks.